2017
DOI: 10.1016/j.jaac.2017.07.780
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Universal Resilience-Focused Interventions Targeting Child and Adolescent Mental Health in the School Setting

Abstract: Systematic Review of Universal Resilience Interventions Targeting Child and Adolescent Mental Health in the School Setting; http://dx.doi.org/10.1186/s13643-015-0172-6; PROSPERO CRD42015025908.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
304
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(364 citation statements)
references
References 95 publications
18
304
0
7
Order By: Relevance
“…We designed CUES‐Ed, drawing on the existing evidence base (e.g. Dray et al., ; Stallard et al., ), as a clinician‐led whole‐class CBT programme for 7–10 year‐olds. Universal, school‐based interventions offer accessibility and economies of scale in delivery, and promote peer support and modelling, normalising mental health vulnerability, without labelling (Stallard et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…We designed CUES‐Ed, drawing on the existing evidence base (e.g. Dray et al., ; Stallard et al., ), as a clinician‐led whole‐class CBT programme for 7–10 year‐olds. Universal, school‐based interventions offer accessibility and economies of scale in delivery, and promote peer support and modelling, normalising mental health vulnerability, without labelling (Stallard et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Interventions focusing on improving children's resilience can decrease the symptoms of anxiety and general psychological distress of surgical patients . These interventions include supporting resilience‐enhancing factors, high connectedness, and cohesion among family members . Sufficient analgesia helps to relieve this distress and enable smooth postoperative recovery …”
Section: Helping Children and Parents Improve Resiliencementioning
confidence: 99%
“…There was also a positive effect for general and social functioning, but not anxiety symptoms, post‐intervention. A recent meta‐analysis has explored the effectiveness of resilience‐based school interventions (including CBT) in improving the mental health of children and adolescents . The authors found a positive effect in reducing both depressive and anxiety symptoms at short‐term follow‐up (up to 11 months), but not beyond .…”
Section: Clinical Perspectivementioning
confidence: 99%
“…A recent meta‐analysis has explored the effectiveness of resilience‐based school interventions (including CBT) in improving the mental health of children and adolescents . The authors found a positive effect in reducing both depressive and anxiety symptoms at short‐term follow‐up (up to 11 months), but not beyond . The meta‐analysis included 12 of the studies used in the updated Cochrane review and 1 study not available at the time of the analysis, a cluster RCT of a universal intervention programme of 1341 adolescents (intervention group n = 665), which did not demonstrate a reduction in depressive symptoms, compared to controls, at 1‐ or 2 years' follow‐up .…”
Section: Clinical Perspectivementioning
confidence: 99%
See 1 more Smart Citation